2022
DOI: 10.3390/polym14030434
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Flexural Properties of PA12/Clay Nanocomposites

Abstract: Polymer nanocomposites consist of a polymer matrix and reinforcing particles that have at least one dimension under 100 nm. The processing of nanocomposite polymers is the most important stage, determining the final properties of nanocomposites. Nanocomposites are now preferentially prepared by melt-mixing using conventional compounding processes such as twin-screw extrusion. Many processing parameters (polymer matrix type, content and type of nanofiller, barrel temperature, screw speed, number and shape of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Table8was used. The p-value (lack of t) greater than 0.05 for the quadratic model indicates the smallness of the lack of t for this model, which can also be seen in the data in the table(Stojšić et al 2022). The values in the R 2 column indicate the determination coe cient.…”
mentioning
confidence: 55%
“…Table8was used. The p-value (lack of t) greater than 0.05 for the quadratic model indicates the smallness of the lack of t for this model, which can also be seen in the data in the table(Stojšić et al 2022). The values in the R 2 column indicate the determination coe cient.…”
mentioning
confidence: 55%
“…Indeed, this feature impacts substantially both the intercalation stage, where the polymer chains diffuse within OMt interlayer space, and the exfoliation stage to achieve the delamination of individual platelets and their diffusion into the melt. 20 We expect that the gemini surfactants will participate actively to these compatibilization process of clay with polymer organic matrix through the establishment of hydrogen-bonding interactions between the amide functions of surfactant molecules and the carbonyl groups of PBS ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The area of science and competition in the preparation of better materials with important characteristics is steadily expanding, and particularly in nanotechnology areas, a vast quantity of studies and improvement has been observed over the last few centuries [ 1 , 2 , 3 ]. Nanotechnology is becoming the largest area of growth in the world [ 4 ].…”
Section: Introductionmentioning
confidence: 99%